Проблеми правового регулювання нетипових видів зайнятості - Гусаров, О. С.; Husarov, O. S. (Науковий вісник публічного та приватного права. - 2023. - Вип. 3. - С. 50-55, 2023)
У статті здійснено аналіз наукових поглядів вчених, які у своїх працях досліджували окремі проблемні питання, пов’язані із правовим регулюванням нетипових видів зайнятості. Запропоновано авторське бачення щодо існуючих теоретичних та практичних проблем у сфері правового регулювання нетипових форм зайнятості в Україні. Наголошено на необхідності внесення змін та доповнень до діючого трудового законодавства, а також розробки нових законодавчих та підзаконних актів, норми яких будуть спрямовані на регулювання праці досліджуваної у статті категорії працівників.

The article analyzes the scientific views of scientists who, in their works, investigated certain problematic issues related to the legal regulation of atypical types of employment. The author’s vision regarding existing theoretical and practical problems in the field of legal regulation of atypical forms of employment in Ukraine is offered. It is emphasized the need to introduce changes and additions to the current labor legislation, as well as the development of new legislative and by-laws, the norms of which will be aimed at regulating the work of the category of employees studied in the article. It was concluded that among the main problems in ensuring the legal rights and interests of both employers and employees are those related to: the lack of a clear distinction between the norms of civil and labor law in the legal regulation of atypical types of employment, which in turn leads to the emergence legal conflicts; insufficiently high-quality regulation of employers’ obligations regarding material and technical support and organization of the activities of employees in non-typical types of employment; with a safety factor, because today there are no effective labor protection mechanisms at the legislative level, which carry out labor activities at home, remotely, etc.; with the absence of a clear legal definition of the prohibition of reducing the amount of remuneration in the absence of a decrease in the amount of workload; the actual lack of an effectively built system of legal regulation of the careers of employees engaged in work in non-typical forms of employment; the uncertainty of dangerous and harmful production (technological) factors, the presence of which makes it impossible to perform work remotely, as well as categories of persons, such as civil servants, who cannot work remotely; legal uncertainty of the content of the main terms that define certain types of atypical types of employment, in particular outsourcing, outstaffing and personnel leasing; with the legal uncertainty of the use of temporary employment, as well as the working hours of employees recruited through private employment agencies, in particular, the uncertainty of the maximum possible duration of employment of such employees, etc.

Проведен анализ научных взглядов ученых, которые в своих трудах исследовали отдельные проблемные вопросы, связанные с правовым регулированием нетипичных видов занятости. Предложено авторское видение существующих теоретических и практических проблем в сфере правового регулирования нетипичных форм занятости в Украине. Отмечена необходимость внесения изменений и дополнений в действующего трудового законодательства, а также разработки новых законодательных и подзаконных актов, нормы которых будут направлены на регулирование труда изучаемой в статье категории работников.
Problems of legal regulation of atypical types of employment
Keywords: трудові відносини; labor relations; трудовые отношения; правове регулювання; legal regulation; правовое регулирование; нетипова зайнятість; atypical employment; нетипичная занятость; трудове законодавство; labor legislation; трудовое законодательство